Managing Couple Conflict During Prenatal Counseling Sessions: An Investigation of Genetic Counselor Experiences and Perceptions. Issue 5 (22nd March 2018) - Schoeffel, Kara; McCarthy Veach, Patricia; Rubin, Karol; LeRoy, Bonnie
Abstract: Research shows couple conflict occurring during prenatal genetic counseling sessions may be challenging for some genetic counselors. Yet, no study has explored couple conflict in depth. The current study investigated genetic counselors' experiences and perceptions of the nature and context of couple conflict in prenatal sessions and counselor conflict management strategies. Sixteen prenatal genetic counselors recruited through the National Society of Genetic Counselors participated in semi‐structured phone interviews asking about how they recognize couple conflict; topics that trigger conflict and when it occurs; individual, cultural, and situational factors associated with conflict; conflict management strategies; and specific examples from their practice. Inductive and cross‐case comparison methods revealed a number of themes. Genetic counselors recognize couple conflict through non‐verbal and verbal cues, and conflict can occur at any time, particularly during decision‐making about testing and test results and during results review of an affected pregnancy. Factors associated with conflict include cultural customs, age, emotional state, religious beliefs, and being forced to attend counseling. Participants identified 23 conflict management strategies classified into five themes: facilitate decision‐making, encourage couple expression, act within one's scope of practice, provide psychosocial support, and support the identified patient. Counselors emphasized that their strategies are couple dependent. Patients may benefit from genetic counselors assessing couple conflict and intervening when it impedes genetic counseling goals. Clinical examples from this study may contribute to informing genetic counselor practice, program curricula, and continuing education workshops.